Development of a sensitive closed batch vessel hydride generation atomic absorption spectrometry method for the determination of cadmium in aqueous samples - Buyukpinar, Cagdas; Bekar, Busra; Maltepe, Esra; Chormey, Dotse Selali; Turak, Fatma; San, Nevin; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2018)
Hydride generation atomic absorption spectrometry was used as a simple, sensitive, and economical method for the determination of cadmium at trace levels. This study includes a stepwise optimization of all parameters that have an impact on the production, transport, and atomization of cadmium hydride for rapid determination due to the unstable nature of the hydride produced. The cell temperature for atomization, pump period, and flow rate of carrier gas were varied, and the best conditions were defined to obtain lower detection limits. In addition, the acid and sodium borohydride concentrations were optimized since they directly affect the production of the cadmium hydride. Under optimum experimental conditions, the hydride generation efficiency was greatly enhanced to record optimized analytical signals. The accuracy of the method was determined by the analysis of a certified reference material, and the results were in good agreement with the certified value. A linear dynamic range for cadmium was observed from 0.10 to 2.0 mu g/L. High sensitivity was obtained with a limit of detection of 0.029 mu g/L.
Keywords: Atomic absorption spectrometry (AAS); cadmium; drinking water; hydride generation; CHEMICAL-VAPOR GENERATION; ONLINE PRECONCENTRATION; HEAVY-METALS; SOIL; LEAD; COPPER; CARCINOGENESIS; EXPOSURE; WATER; Chemistry; Instruments & Instrumentation